Optimizing Cabbage Yield through integrated biochar and cow urine applications: Cabbage Yield through integrated biochar and cow urine (Bangladesh Journal of Agriculture, 2024)
This experiment was conducted at the Germplasm Center of Patuakhali Science and Technology University from November 2019 to January 2020. The objective  of this research was to optimize  cabbage production by incorporating  biochar-based fertilizers and cow urine and reducing dependence on chemical fertilizers.. A Randomized Complete Block Design (RCBD) was employed. The treatments consisted of : T1 = control, T2 = biochar + cow urine, T3 = recommended manures, T4 = recommended fertilizers, T5 = recommended fertilizers + biochar + cow urine, and T6 = recommended manures and fertilizers. The result showed a substantial impact of biochar-based fertilizers, particularly when combined with cow urine and recommended manures and biochar (T5). Significant improvements were observed in plant height (33.55 cm), leaf no. (22.84), plant spread (64.52 cm²), leaf weight (0.25 kg plant⁻¹), and length of the stem (4.77 cm) as well as  cabbage head characteristics, including increased length (20.00 cm), diameter (24.63 cm), weight (2.17 kg), and overall head yield (77.93 t/ha). The findings underscore the potential of integrating biochar-based fertilizers and cow urine, in conjunction with recommended manures to enhance cabbage growth and yield reduce reliance on chemical fertilizers, and mitigate environmental risks.Bangladesh J. Agri. 2024, 49(1): 128-135